AKAD KERJASAMA MERTELU PADA BIDANG PERTANIAN DI BLOK BALIR II DITINJAU DARI HUKUM ISLAM - Rizqi Arifan Zulianto; Irvan Iswandi (Melati Institute, 2022)
This undergraduate thesis discusses how the implementation of the Mertelu cooperation contract in the agricultural sector in the Balir II Block in terms of Islamic Law. The practice of mertelu farming cooperation has long been carried out by the community. Mertelu is a cooperation in the field of agriculture in which one party acts as a land manager and the other party acts as a land owner. This cooperation occurs because one party has the power to manage the land but does not own the land, while the land owner owns the land but does not have the power to manage the land. The focus of the research in this undergraduate thesis is how is the implementation and how is the review of Islamic law regarding the implementation of the Mertelu agricultural cooperation contract which was carried out in the Balir II Block, Mekarjaya Village, Gantar District, Indramayu Regency?. This undergraduate thesis used a qualitative research method with a field research approach. There were two sources of data in this study, namely primary data sources resulting from interviews with farmers and residents who have carried out this collaboration or who know exactly about this collaboration Meanwhile, secondary data sources in this undergraduate thesis came from documents, books, notes, and etc. Data analysis was carried out using a qualitative approach. Based on the results of the study, it was concluded that the practice of Mertelu cooperation in the agricultural sector carried out by the Balir II Block community, Mekarjaya Village, Gantar District, Indramayu Regency was not in accordance with the provisions of Islamic law. This is due to the absence of one fundamental requirement in Islam, namely the recording of all non-cash activities.